2022
DOI: 10.32604/cmes.2022.019075
|View full text |Cite
|
Sign up to set email alerts
|

An Acceptance Model of Using Mobile-Government Services (AMGS)

Abstract: In recent years, the telecommunications sector is no longer limited to traditional communications, but has become the backbone for the use of data, content and digital applications by individuals, governments and companies to ensure the continuation of economic and social activity in light of social distancing and total closure in most countries in the world. Therefore, electronic government (e-Government) and mobile government (m-Government) are the results of technological evolution and innovation. Hence, it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 28 publications
1
9
0
Order By: Relevance
“…This result can be attributed to the fact that when a bank client finds his/her interactions with a mobile banking application to be simple, understandable and clear, his/her attitude toward that application will improve. Our findings are in accordance with those of prior studies [66][67][68], which noted that perceived ease of use is the strongest predictor in the TAM model and has positive effect on attitude toward such technology. Studies on e-banking [92][93][94] have confirmed that perceived ease of use has a positive relationship with intention to use e-banking system.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This result can be attributed to the fact that when a bank client finds his/her interactions with a mobile banking application to be simple, understandable and clear, his/her attitude toward that application will improve. Our findings are in accordance with those of prior studies [66][67][68], which noted that perceived ease of use is the strongest predictor in the TAM model and has positive effect on attitude toward such technology. Studies on e-banking [92][93][94] have confirmed that perceived ease of use has a positive relationship with intention to use e-banking system.…”
Section: Discussionsupporting
confidence: 93%
“…In addition, when clients find that interactions with a mobile banking application are simple, understandable and clear, this will improve their intention to use that application. Prior studies [66][67][68] have mentioned that perceived ease of use is the strongest predictor in the TAM model and has positive effect on intention to use technology. Studies on ebanking [69,70] have confirmed that perceived ease of use has positive relationship with intention to use e-banking systems.…”
Section: Perceived Ease Of Usementioning
confidence: 99%
“…The UTAUT emerged through a synthesis of eight foundational models, encompassing theories like the Innovation Diffusion Theory (IDT), Theory of Reasoned Action (TRA), and others [21]. It has found application in diverse domains, including e-learning, e-governance, and ebanking [21][22][23][24]. However, its adaptability to the unique realm of solar PV technology adoption within Saudi housing in Makkah remains largely unexplored.…”
Section: Evolving Tam With Utautmentioning
confidence: 99%
“…The concept of e-Government, which leverages information and communication technology (ICT), mobile technology, and the internet, is instrumental in delivering essential services to citizens, enhancing public agency performance, fostering public participation, and integrating citizens into broader social development processes (Abu-Shanab, 2017). Within this digital landscape, m-Government emerges as a pivotal dimension, allowing citizens to access government services seamlessly through mobile devices, meeting their information needs ubiquitously (Althunibat et al, 2022).…”
Section: Introductionmentioning
confidence: 99%